2017
DOI: 10.5194/acp-17-14543-2017
|View full text |Cite
|
Sign up to set email alerts
|

The SPARC water vapor assessment II: intercomparison of satellite and ground-based microwave measurements

Abstract: Abstract. As part of the second SPARC (Stratospheretroposphere Processes And their Role in Climate) water vapor assessment (WAVAS-II), we present measurements taken from or coincident with seven sites from which ground-based microwave instruments measure water vapor in the middle atmosphere. Six of the ground-based instruments are part of the Network for the Detection of Atmospheric Composition Change (NDACC) and provide datasets that can be used for drift and trend assessment. We compare measurements from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 35 publications
0
27
1
Order By: Relevance
“…(see, e.g., Nedoluha et al, 2017). We have determined the relative contributions of the two sources of H 2 O using recent satellite observations of H 2 O and CH 4 from the instrument SOFIE (Solar Occulation For Ice Experiment) on the AIM satellite (Aeronomy of Ice in the Mesosphere) at the stratopause (H 2 O = 7.5 ppmv and CH 50km 4 = 100 ppbv; Rong et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…(see, e.g., Nedoluha et al, 2017). We have determined the relative contributions of the two sources of H 2 O using recent satellite observations of H 2 O and CH 4 from the instrument SOFIE (Solar Occulation For Ice Experiment) on the AIM satellite (Aeronomy of Ice in the Mesosphere) at the stratopause (H 2 O = 7.5 ppmv and CH 50km 4 = 100 ppbv; Rong et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The H 2 O trends of Figure are smaller than the secular trends from the model study of Garcia et al () and somewhat smaller than the analyzed trends from HALOE data in Randel et al (), both for the time span of 1992–2002. On the other hand, Nedoluha et al () reported on H 2 O trends at 0.46 hPa for 1996 through 2005 from ground‐based microwave measurements at two sites (Mauna Loa, Hawaii at 19.5°N, 204°E, and Lauder, New Zealand at 45°S, 170°E). Their trends are between ±1% per decade and are consistent with observed trends of H 2 O entering the lower stratosphere.…”
Section: Linear Trends In H2omentioning
confidence: 99%
“…Section 5 contains the updated results of the responses of H 2 O and temperature to the solar forcings and extends those findings through the lower mesosphere. Section 6 shows the associated H 2 O trends and compares them with ones reported by Nedoluha et al (2017) for 1992-2005 from two ground-based microwave radiometer sites. Section 7 reports on results from a separate simultaneous temporal and spatial (STS) analysis method that accounts for diurnal effects and for any biases due to changes in the sampling with latitude from HALOE.…”
Section: Introductionmentioning
confidence: 99%
“…Global warming is predicted to increase tropospheric lightning activity (5–10% for every 1° of warming) (Krause et al, ; Michalon et al, ; Price & Rind, ; Romps et al, ; Trapp et al, ) although the prediction has a large uncertainty in the lightning parameterization (Finney et al, ). Long‐term trends of increase in mesospheric carbon dioxide (CO 2) and water vapor (H 2O) have been reported owing to recent improvement in the accuracy of global measurements (Chandra et al, ; Nath et al, ; Nedoluha et al, ; Qian et al, ). These trends, approximately +5.5% of CO 2 and <10% of H 2O per decade, are related to anthropogenic CO 2 and methane (CH 4) emissions, respectively, and affect radiative forcing and mesospheric composition.…”
Section: Estimation Of Ho 2 Amount Produced By Sprite Eventsmentioning
confidence: 99%